Infusing Aboriginal Perspectives in Cyber Education - Shannahan, John; Ahmed, Mohiuddin (EAI Endorsed Transactions on e-Learning, 2025)
While human factors are important in cyber security, the discipline has largely not explored incorporating indigenous perspectives—or, more specifically, in an Australian context, Aboriginal perspectives—in its curricula. In this paper, we introduce a promising approach for aligning Aboriginal perspectives with the needs of cyber security graduates and incorporating diverse perspectives into cyber degrees. The approach advocates for the centrality of good curriculum design fundamentals: backward design, constructive alignment, and student outcomes. The paper ends by reflecting on challenges and lessons from the first implementation and review of the material. It provides recommendations for other cyber practitioners exploring ways of incorporating indigenous perspectives in their teaching.
Keywords: First Nations Perspectives; Indigenous Perspectives; Cyber Security; Cyber Education; Computer Science Education; Strength and Deficit-based Discourse